Tracing Digital Learning Trajectories in Biology Education ‎Across the Life Course: A Qualitative Study of Learners’ ‎Transitions and Meaning Making - Akbar Handoko; Denny Philip; HuongVu (WISE Pendidikan Indonesia, 2025)
The increasing integration of digital technologies in science education has reshaped how biology is learned across formal and informal contexts; however, existing research has predominantly focused on short-term outcomes, offering limited insight into how digital biology learning evolves across individuals’ life courses. This study aims to explore digital biology learning experiences through a life-course perspective, examining learning trajectories, critical transitions, and meaning-making processes across different stages of life. Employing a qualitative narrative inquiry design, data were collected from 15 participants through in-depth semi-structured interviews, written reflections, and digital learning artifacts, and analyzed using thematic narrative analysis informed by life-course theory. The findings reveal three interconnected themes: evolving digital learning trajectories characterized by a shift from teacher-directed to self directed learning, critical transitions that reshape engagement with digital biology learning, and dynamic processes of meaning-making that increasingly connect biological knowledge to everyday life contexts such as health and environmental awareness. These results demonstrate that digital biology learning is a cumulative and adaptive process shaped by temporal, contextual, and biographical factors rather than isolated instructional events. The study contributes to the literature by integrating life-course theory with digital biology education research, highlighting the importance of designing flexible and learner-centered digital learning environments that support continuity, agency, and lifelong engagement with biological knowledge, with implications for educators, curriculum developers, and education policymakers seeking to promote sustainable lifelong science learning.